S11 Identification and attendance of a high-risk cohort in a lung cancer screening demonstration pilot. (15th November 2017) - Ruparel, M; Quaife, SL; Dickson, JL; Bhowmik, A; Taylor, MN; Ahmed, A; Shaw, PJ; Burke, S; Soo, MJ; Devaraj, A; Navani, N; Duffy, SW; et al.
Abstract : Introduction: Lung Cancer screening by Low-Dose CT (LDCT) has been shown to reduce mortality, though exactly how best to implement this is unclear. Uptake to screening trials has generally been low, particularly in those at highest risk of lung cancer. The Lung Screen Uptake Trial is a UK based dual centre LDCT randomised controlled screening trial of a modified invitation strategy versus a standard approach in a population with high levels of socioeconomic deprivation. Methods: Patients were identified as 'high-risk' primarily by age and smoking history on a predesigned EMIS-Web search and subsequently invited on behalf of their general practitioner (GP) to a 'lung health check' appointment. Those attending were offered enrolment into the study and a LDCT if they met the required threshold of lung cancer risk. This abstract focuses on the mode of recruitment via general practice. Results: Potentially eligible participants were recruited from 16 GP surgeries serving a population of 1 55 034. Of these, 8.7% were in the required age range of 60–75% and 98.9% of those had smoking status recorded. A mean of 32.2% (SD 3.8) of those aged 60–75 had been recorded as a current smoker in the preceding 15 years. A total of 1997 patients, who had been recorded as current smokers within the past 5 years were invited. Uptake to the study was 50.3% (n=1005) of all those invited. 765 underwent a LDCT examination (figure 1 ). In 10.3% of patients the smoking history was confirmed to be too light for CT screening, despite GP records suggesting otherwise. Conclusions: Smoking status was found to be very well recorded in primary care records, providing a feasible method for initial selection of those eligible for screening. However we also showed the importance of confirmation of smoking history, something that might be done prior to invitation in screening programmes. This study observed a high rate of attendance when compared to previous LDCT screening trials. The explanation for this observed difference is likely to be multifactorial, though one key factor, unique to this study, is that the invitation to participate came from patients' own GP.